Crack propagation behavior and mechanism of coarse-grained copper in cyclic torsion with axial static tension. (February 2020) - Xu, J.X.; Li, R.H.; Zhang, P.; Zhang, Z.F.
Highlights: Axial static tension can affect the direction of Stage I crack growth. Axial static tension can cause the transition of crack growth from Stage I to Stage II. The effect of axial static tension on crack growth depends on strain amplitude. The micro-mechanisms produced by axial static tension on crack growth are proposed. Abstract: In order to essentially study the influence of axial static tension on torsional fatigue crack propagation, cyclic torsion with and without axial static tension are carried out for coarse-grained copper. Results show that static tension affects the crack propagation behavior of coarse-grained copper in two ways: it can not only affect the growth direction of Stage I crack growth, but can also lead to the transition of surface crack from Stage I to Stage II. The micro-mechanisms produced by mean stress on crack propagation, particularly the transition mechanism from Stage I to Stage II crack growth, are analyzed.